Evisceration of Right Pulmonary Lobe after Dog Bite Injury - Ferreira, Manoel Luiz; Rodrigues, Allana Ornellas; Rousso Filho, Raul; Reis da Costa, Valeria Duarte; Schanaider, Alberto (Acta Scientiae Veterinariae, 2019)
Background: Pneumothorax is the presence of free air in the pleural cavity. Air in the thoracic cavity causes respiratory discomfort, severe hypoxemia, decreased venous return, and haemodynamic instability, and it may lead to death. Pneumothorax can be triggered by wounds from firearm projectiles, bladed weapons, or sharp or piercing objects, as well as bites and barotrauma. The diagnosis of open pneumothorax is based on anamnesis, in combination with clinical signs observed on physical examination. The objective of this report is to discuss the relevance of clinical-surgical management to adequately treat evisceration of the pulmonary lobe caused by a bite in the thoracic region of a female dog. Case: This report discusses a 15-year-old female canine weighing approximately six kg with a history of wounds in the thoracic region and respiratory difficulty after being bitten by another dog. On clinical examination, she presented with a bruised wound in the right thoracic region and another in the scapular region. The examination revealed evisceration of the right cranial lung lobe, which exhibited atelectasis. The animal was immediately referred to the Surgical Center. Anaesthesia was induced using propofol 2.0 mg/kg combined with ketamine hydrochloride 2.0 mg/kg, followed by intubation and maintenance under inhalation anaesthesia with isoflurane and 100% oxygen and fentanyl 2.5 mcg/kg every 15 min. The temperature, non-invasive blood pressure, cardiac and respiratory frequency, pulse oximetry, capnography and electrocardiogram were monitored. Tricotomy and antisepsis of the wound were performed with 0.9% NaCl and 2% chlorhexidine. The eviscerated pulmonary lobe was immersed in saline solution, and positive pressure insufflation was performed in the inhalation circuit to verify the presence of perforation of the eviscerated lung, which was not observed. The lobe was repositioned in the correct anatomical location in the thoracic region, noting that there was no further damage beyond the blunt wound with laceration of the intercostal muscles. The thoracic cavity was washed with saline solution, which was aspirated prior to thoracorrhaphy with a 2-0 nylon suture, applied with mass-separated stitches covering the pleura and intercostal musculature. When the last stitch of the thoracorrhaphy was placed, the anaesthesiologist kept the lung inflated. A No. 8 drain was fixed in a tobacco pouch coupled to a three-way tap in the region between the seventh and eighth ribs. The adipose panicle was stitched with a 2-0 910 polygalactine suture and continuous pattern, and the skin was sutured with a 2-0 nylon suture using Wolff stitches. The dressing consisted of a bandage around the thorax for 48 h, when the drain was removed. Meloxicam 0.1 mg/kg, ceftriaxone 30 mg/kg per day and metronidazole 10 mg/kg every 12 h were prescribed postoperatively for seven days. For analgesic therapy, 0.3 mg/kg morphine sulfate was used every six hours for 48 h, dipyrone 25 mg/kg was used for 72 h, and tramadol hydrochloride 2.4 mg/kg was used every eight hours for five days. At the site of the dressing, there was topical application every 48 hours of fibrinolysin combined with chloramphenicol. Discussion: Open thoracic injuries with pulmonary evisceration are always considered a serious and a death threat. An early care by a specialized team is of paramount importance in restoring respiratory and cardiovascular parameters with a better prognosis.